Sport Policy Systems and Sport Federations : A Cross-National Perspective - Scheerder, Jeroen; Willem, Annick; Claes, Elien (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book explores the organisation and structure of sport in and beyond Europe. Drawing upon up-to-date data, the collection's main focus lies on the relationship between public sport policy structures and sport (con)federations. The authors present thirteen country-speciﬁc contexts wherein sport policy systems are embedded. This evidence provides in-depth descriptions and analyses within a solid academic and theoretical framework. This volume will be of interest to students and scholars of Sociology of Sport, Sport Management and Sport Policy.
Keywords: Social sciences.; Sports.; Sports -- Economic aspects.; Sports -- Sociological aspects.; elektronické knihy; electronic books